Support any friend : Kennedy's Middle East and the making of the U.S.-Israel alliance - Bass, Warren (Council on Foreign Relations book., 2003)
At the Cold War's height, John F. Kennedy set precedents that continue to shape America's encounter with the Middle East. Kennedy was the first president to make a major arms sale to Israel, the only president to push hard to deny Israel the atomic bomb, and the last president to reach out to the greatest champion of Arab nationalism, Egyptian President Jamal Abdul Nasser. Now Warren Bass takes readers inside the corridors of power to show how Kennedy's New Frontiersmen grappled with the Middle East. He explains why the fiery Nasser spurned Washington's overtures and stumbled into a Middle Eas.